(untitled) (Scientific journal of the Fergana State University, 2024)
Among the microfields connected to the semantic field of "crime" in the English and Uzbek languages, the content of the microfield of "murder" is superior due to the diversity of its elements. Although it has a subtle negative meaning, this micro-field, which covers the lifestyles and peculiarities of the long past of the two peoples, is verbalized differently in the spoken languages. In this article, the central and peripheral members of the microfield are analyzed semantically. On the basis of mutual relations between them, the merging of lexical units representing the semantics of "murder" into one microfield is based. If the lexeme "murder" is considered as the core element of the "murder" microfield in the studies carried out in English, the expression of the semantics of "crime" in the Uzbek language has not been studied on the basis of the field theory. The author conducted a survey with the 2nd-level graduate students of Fergana State University and determined the central element of the microfield of "murder", which is the most frequently used lexical unit in the communication of students of English as a foreign language. It is proven that the results are different and are influenced by the global English language.